Multi‐compartment metabolomics and metagenomics reveal major hepatic and intestinal disturbances in cancer cachectic mice. Issue 2 (17th February 2021) - Pötgens, Sarah A.; Thibaut, Morgane M.; Joudiou, Nicolas; Sboarina, Martina; Neyrinck, Audrey M.; Cani, Patrice D.; Claus, Sandrine P.; Delzenne, Nathalie M.; Bindels, Laure B.
Abstract: Background: Cancer cachexia is a multifactorial syndrome characterized by multiple metabolic dysfunctions. Besides the muscle, other organs such as the liver and the gut microbiota may also contribute to this syndrome. Indeed, the gut microbiota, an important regulator of the host metabolism, is altered in the C26 preclinical model of cancer cachexia. Interventions targeting the gut microbiota have shown benefits, but mechanisms underlying the host–microbiota crosstalk in this context are still poorly understood. Methods: To explore this crosstalk, we combined proton nuclear magnetic resonance ( 1 H‐NMR) metabolomics in multiple compartments with 16S rDNA sequencing. These analyses were complemented by molecular and biochemical analyses, as well as hepatic transcriptomics. Results: 1 H‐NMR revealed major changes between control (CT) and cachectic (C26) mice in the four analysed compartments ( i.e . caecal content, portal vein, liver, and vena cava). More specifically, glucose metabolism pathways in the C26 model were altered with a reduction in glycolysis and gluconeogenesis and an activation of the hexosamine pathway, arguing against the existence of a Cori cycle in this model. In parallel, amino acid uptake by the liver, with an up to four‐fold accumulation of nine amino acids ( q ‐value <0.05), was mainly used for acute phase response proteins synthesis rather than to fuel the tricarboxylic acid cycle and gluconeogenesis. We also identified a 35% reduction in hepatic carnitine levels ( q ‐value <0.05) and a lower activation of the phosphatidylcholine pathway as potential contributors to the hepatic steatosis present in this model. Our work also reveals a reduction of different beneficial intestinal bacterial activities in cancer cachexia. We found decreased levels of two short‐chain fatty acids, acetate and butyrate (72% and 88% reduction in C26 caecal content; q ‐value <0.001), and a reduction in aromatic amino acid metabolites, which may contribute to the altered intestinal homeostasis in these mice. A member of the Ruminococcaceae family (ASV 2) was identified as the main bacterium responsible for the drop in butyrate. Finally, we report a two‐fold intestinal transit acceleration ( P ‐value <0.001) as a key factor shaping the gut microbiota composition and activity in cancer cachexia, which together lead to a faecal loss of proteins and amino acids. Conclusions: Our work highlights new metabolic pathways potentially involved in cancer cachexia and further supports the interest of exploring the gut microbiota composition and activity, as well as intestinal transit, in cancer patients with and without cachexia.